Adding Perplexity to Rarity: Diffuse S100-Protein and SOX10 Expression in a Molecularly Confirmed PAX7-Positive Primary Cutaneous Ewing Sarcoma. (December 2021) - Parra, Ourania; Thuraisingam, Ravina; Baker, Michael L.; Kerr, Darcy A.; Linos, Konstantinos
Abstract : Abstract: Primary cutaneous Ewing sarcoma (EWS) is a very rare neoplasm that shares similar morphologic, immunohistochemical, and molecular features with its osseous counterpart. Herein, we present an extraordinarily rare case of PAX7-positive cutaneous EWS in a 9-year-old girl that was also diffusely positive for SOX10 and S100-protein. Next generation sequencing detected the EWSR1-FLI1 fusion supporting the diagnosis, which was further validated by break-apart EWSR1 fluorescence in situ hybridization. Diffuse S100-protein and SOX10 expression has been reported only in a handful of cases of EWS and may pose significant diagnostic challenges for dermatopathologists. PAX7 is a recently introduced marker, which is highly sensitive for EWS and can potentially have discriminatory power in the differential diagnosis of cutaneous undifferentiated round blue cell tumors.